2010
DOI: 10.3136/fstr.16.607
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Repeated Sodium Hypochlorite Exposure on Chlorine Resistance Development in Escherichia coli O157:H7

Abstract: Chlorine water has been widely used to reduce viable bacterial contamination on food surfaces and sanitize processing facilities. The emergence and spread of microorganisms with reduced susceptibility to antimicrobial agents is a major public health problem. This in vitro study was designed to evaluate the possibility that E. coli O157:H7 can acquire chlorine resistance and subsequent induction of crossresistance to chlorine water. In addition, the occurrence of spontaneous chlorine resistance mutations or a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, in this study bacterial sensitivity may have been altered by the protocol's intermediate sub-culturing step in rich growth media between each chlorine exposure (Haas and Morrison, 1981). Similarly, Inatsu et al (2010) showed no change in resistance against sodium hypochlorite among E. coli cultures repeatedly treated with the disinfectant. Fewer studies investigated resistance development in response to other disinfectants.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, in this study bacterial sensitivity may have been altered by the protocol's intermediate sub-culturing step in rich growth media between each chlorine exposure (Haas and Morrison, 1981). Similarly, Inatsu et al (2010) showed no change in resistance against sodium hypochlorite among E. coli cultures repeatedly treated with the disinfectant. Fewer studies investigated resistance development in response to other disinfectants.…”
Section: Introductionmentioning
confidence: 73%
“…Collectively, defense mechanisms alter bacterial physiological responses at the phenotypic and, often, the genetic level, which decreases the susceptibility of subsequent generations to chemical exposure. However, reports of mechanisms contributing to bacterial resistance/tolerance against disinfectants in the literature are scarce (Farkas-Himsley, 1964;Haas and Morrison, 1981;Leyval et al, 1984;Hoff and Akin, 1986;Inatsu et al, 2010;Gundlach and Winter 2014). Additionally, the majority of studies have focused on resistance development against chlorine-based disinfectants due to their widespread use, though the studies show contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…Bactericidal effectiveness of ozone microbubble water in vitro The experimental methods were the same as previously published (Inatsu et al, 2010a), except for small modifications. The ozone microbubble water (OMBW) was purchased from Nano Industry Development Co. Ltd. (Miyagi, Japan) and was used within a month.…”
Section: Methodsmentioning
confidence: 99%
“…The washing water was removed using a salad spinner for 1 min, and the viable cells of the samples were enumerated by the pour plate method after 1 min of subjection to a stomacher machine (Gunze industry, MC-D type 400D). The residual bactericidal activity of the washing solution was also measured by exposing PBS-washed E. coli cells for 3 min (Inatsu et al, 2010a;Elano et al, 2010). Instead of the washing treatment, exposing the vegetables to 100 mg/L of GO in plastic bags was also performed.…”
Section: Introductionmentioning
confidence: 99%